Phytochemistry, pharmacological activities and traditional uses of Emblica officinalis: A review (International Current Pharmaceutical Journal, 2016)
From the ancient time, plants have been playing a key role for the betterment of mankind presenting as an extraordinary source of natural medicine. The complexity in formulating chemical based drugs as well as their health related side effects and uprising cost has led worldwide researchers to focus on medicinal plant research. Bangladesh has a vast repository of diverse plant species where about five thousand plants species have been claimed as having significant medicinal values. The researched papers on medicinal plants publishing from last few decades mention the activities of different plant bioactive compounds that are used widely in the treatment of various human ailments. Emblica officinalis is reported to possess bioactive compounds like tannins, flavonoids, saponins, terpenoids, ascorbic acids and many other compounds which are confirmed to have diverse pharmacological activities like antimicrobial, antioxidant, anti-inflammatory, radio-protective, hepatoprotective, antitissuive, immunomodulatory, hypolipedemic and many other activities. This medicinal plant is also reported to have anticancer, anti HIV-reverse transcriptase, antidiabetic, antidepressant, antiulcerogenic, wound healing activities and so forth. The current review paper summarizes the phytochemical constituents, pharmacological activities and traditional uses of the plant Emblica officinalis.Hasan et al., International Current Pharmaceutical Journal, January 2016, 5(2): 14-21